Thymoquinone ameliorates some endocrine parameters and histological alteration in a rat model of polycystic ovary syndrome - Sima Taghvaee Javanshir; Parichehreh Yaghmaei; Zahra Hajebrahimi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Polycystic ovary syndrome (PCOS) is a common form of the endocrine disease which is associated with metabolic dysfunction. PCOS and type 2 diabetes mellitus are related in multiple aspects and are similar in many pathological features. Anti-diabetic effects of Nigella sativa and protective effects of it on reproductive system have been suggested in some reports. Objective: The aim of current study was to evaluate the effects of thymoquinone, the main components of Nigella sativa, on PCOS model of rats. Materials and Methods: Intraperitoneal injection of estradiol valerate for 25 days was used to induce PCOS in Wistar rats, followed by intraperitoneal administration of 8 and 16 mg/kg thymoquinone for 30 days. Rats were divided into 5 groups; control, sham or PCOS, experiment-1 (PCOS and 8 mg/kg thymoquinone), experiment-2 (PCOS and 16 mg/kg thymoquinone), and metformin (PCOS and metformin administration, 100 mg/kg) groups. All of the animals were subjected to serum biochemical analysis of blood and histopathological study of ovaries. Results: Estradiol valerate induced PCOS while administration of thymoquinone recovered it. The body weight, ovarian morphology, and ovulation had been improved and the serum biochemical parameters including glucose, triglyceride, total cholesterol, low-density lipoprotein, high-density lipoprotein, luteinizing hormone, and follicle stimulating hormone were reversed after thymoquinone intervention. Conclusion: Our data suggest that thymoquinone has improvement effects on an ovarian function and ovulation in the PCOS rat model. Therefore, thymoquinone and Nagilla sativa could be used as a protective agent and as an adjunct treatment in PCOS patients